CONCEPTUALISATION OF KARELIAN AND FINNISH RUNIC HERITAGE: A CASE STUDY (BASED ON MUSICAL MATERIAL OF THE CANTATA KANTELETAR BY EDWARD PATLAYENKO AND THE ORATORIO KALEVALA BY ROMAN ZELINSKY) (Mūzikas akadēmijas raksti, 2024)
Two masterpieces are viewed below, works by contemporary Karelian composers. The lyrical genre of Elias Lönnrot’s Kanteletar has attracted Edward Patlayenko, disciple of the Petersburg composers’ school. He selected 6 of 652 runes from Kanteletar, translated by Yosif Brodsky, Valery Bryusov, Aino Hurmevaara. His musical masterpiece was conceived as dispersed double fugue with songs-intermedia. Kalevala by Roman Zelinsky is based on the Russian translation of Kalevala epos by Leonid Belsky. It outlines the keynote runes of the epos: No. 7, 9, 44, 42. Roman Zelinsky, ethnographer, musicologist, raised in Slavonic culture, intended to comprehend, conceptualise the cultural space of the Finno-Ugric region. Deeply focusing on ethnic identity of Finno-Ugric culture, in 1984 he participated in the expedition through the Kalevala region dedicated to the 150th anniversary of Kalevala (1985). Based on sociological and psychological particularities of the composers, the distinctive features of their music masterpieces are being outlined.